An Absorption Spectral Study of 4f-4f Transitions for the Interaction of Pr(III) with Different Amino Acids in Aqueous and Aquated Organic Solvents - Debecca Devi, H.; David Singh, Th.; Yaiphaba, N.; Sumitra, Ch.; Indira Devi, M.; Rajmuhon Singh, N. (Asian Journal of Chemistry, 2010)
By employing absorption difference and comparative absorption spectrophotometry, the interactions of Pr(III) with DL-valine, L-leucine, L(–)-hydroxyproline, DL-alanine, L(+)-arginine and β-alanine in aqueous and different aquated organic solvents have been discussed. The magnitude Of various electronic spectral parameters like Slater-Condon (Fk), Racah (Ek), Lande factor(ξ4f), nephelauxetic ratio (β), bonding (b½), percentage covalency (δ) and intensity parameters like oscillator strength (P) and Judd-Ofelt electric dipole intensity (Tλ) parameters have been evaluated using partial and multiple regression analysis following linear curve analysis and Gaussian curve analysis. The changes in the oscillator strengths of the different 4ƒ-4ƒ transitions and experimentally determined Judd-Ofelt parameters (Tλ) are going to explain nature of binding of lanthanide with different ligands in aqueous and different aquated organic solvents.